Impact of correlated samples loss on VoIP quality - Klimo, Martin; Bachratá, Katarína (Univerzita Pardubice, 2006)
Quality of the IP telephony service can be measured as a composition of many parametres. Some of the parametres of quality of IP telephony service can be measured by secondary characteristics of difference between received and transmitted signal. The aim of this paper is to derive estimations for mean power of noise. Using non orthogonal basis the speech signal can be modeled as a cyclostationary random proces. The case of zero sample stuffing is studied. The packet loss is modeled as a correlated samples loss. As a mathematical model of this correlation the Gilbert model is used.
Vplyv korelovaných strát na kvalitu VoIP
Keywords: IP telephony service; speech signal; Quality; mean power of noise